Awareness, knowledge, attitude and preventive practice of leptospirosis among healthy Malaysian and non-Malaysian wet market workers in selected urban areas in Selangor, Malaysia - Samsudin, Suhailah; Saudi, Siti Nor Sakinah; Masri, Siti Norbaya; Ithnin, Nur Raihana; Tengku Jamaluddin, Tengku Zetty Maztura; Awang Hamat, Rukman; Wan Mohammad, Wan Mohd Zahiruddin; Shafei, Mohd Nazri; Sukeri, Surianti; Daud, Aziah; Abdullah, Nurul Munirah; Nozmi, Noramira; et al. (MDPI, 2020)
Leptospirosis has been reported as an endemic in most tropical countries. Among high risk occupations, leptospirosis includes workers in agriculture and domestic animal industries. Environmental hygiene in the wet market has established a link between the presence of rodents with probability of leptospirosis infection. This study was aimed to compare the level of knowledge, attitude and preventive practice against leptospirosis between healthy Malaysian and non-Malaysian wet market workers in selected wet markets in urban areas of Selangor. A cross-sectional study in the determined area was conducted with the participation of 147 respondents. The respondents were randomly chosen from the list provided by the state agency that regulates these markets. A self-administered bilingual validated questionnaire (English and Bahasa Melayu) was distributed to the selected respondents. There were 68 (48.3%) Malaysian respondents and 79 (53.7%) non-Malaysian respondents. The majority of them were males, who attained formal education and were less than 40 years old. Meanwhile, the respondents earned less than RM3000. Among the Malaysian respondents, 80.9% were aware of leptospirosis as compared to 17.7% of the non-Malaysian colleagues (p < 0.05). All items of knowledge showed that the Malaysian respondents scored higher as compared to non-Malaysian respondents. On attitude towards infection prevention, most Malaysian respondents had a positive attitude, while most non-Malaysian respondents had undecided perception on the majority of crucial attitude items. In practicing preventive measures, there was a marked significant difference in proportion between Malaysian and non-Malaysian respondents for items on “Specific Protection and Isolation at Source.” There was a significant gap on knowledge, attitude and preventive practice among Malaysian workers as compared to non-Malaysian workers. Therefore, it was highly recommended the health promotion implementation should also provide specific focus on non-Malaysian workers.